Higher Education Institutional Libraries in the Digital Era Suan Dusit University - Kitlert, Thipsuda; Chaleysub, Sukum; Janthon, Ua-aree; Tungdamnernsawad, Supaporn (Mahachula Academic Journal, 2025)
This academic article aimed to analyze knowledge about the development of higher education institutional libraries in the digital era, covering concepts, global trends, challenges, and exemplary case studies. Analysis of related literature found that higher education libraries in the digital era were transitioning from traditional information resource repositories to collaborative learning spaces. The role of librarians changed from book custodians to learning facilitators and instructors of information and technology skills that enhanced user experiences. Major challenges that libraries faced included declining traditional users, budget and resource constraints, digital resource management and intellectual property issues, as well as changing behaviors of new generation learners who grew up with digital technology. The "One World Library (OWL)" concept case study demonstrated a paradigm shift in the learning ecosystem with the "Open Wonder Learn" philosophy, expanding learning spaces to cover the entire university, and creatively integrating technology with physical spaces. Success factors for library transformation included clear leadership and vision, effective change management, staff skill development and organizational culture change, appropriate use of technology, and user participation.